CHIP Decline Is Associated With Isoflurane-Induced Neurodegeneration in Aged Mice - Xu, Qiaoqiao; Xiong, Juan; Xu, Li; Wu, Yuanyuan; Li, Man; Li, Qinqin; Jiang, Tao; Luo, Ailin; Zhang, Yi (Frontiers in Neuroscience, 2022)
Perioperative neurocognitive disorders (PND) commonly occur in elderly patients, and isoflurane could be a risk factor. During the pathogenesis of neurodegeneration, the ubiquitin–proteasome system (UPS) participates in the process of aging, which affects synaptic plasticity and synaptic function. However, whether UPS is involved in the etiology of PND is unclear. In this study, we examined the expression change of ubiquitin E3 ligase protein carboxyl-terminus of Hsc70-interacting protein (CHIP) and the function turbulence of UPS in isoflurane-exposed aged mouse to illustrate the role of UPS in PND. Neurodegenerative behavioral changes were shown in isoflurane-exposed aged mice and correlated with neuropathological changes manifested with reduced number of intersections and spine density in the cortex. Ubiquitin function was decreased while the apoptosis was activated, and CHIP protein expression decline altered synapsin expression and phosphorylation associated with the neurodegeneration in isoflurane-induced PND. Aging was the big important factor. And it remained consistent with the synapsin phosphorylation/dephosphorylation level changes in CHIP knock-down N2a cells. Per our observation, the decline in CHIP protein expression and synaptic degeneration might reveal the reason for synaptic degeneration in the underlying pathogenesis of PND caused by isoflurane.